Healthcare utilisation and disclosure of injecting drug use among clients of Australia's needle and syringe programs. (2nd April 2013) - Islam, M. Mofizul; Topp, Libby; Iversen, Jenny; Day, Carolyn; Conigrave, Katherine M.; Maher, Lisa
Abstract: Background : People who inject drugs (PWID) report limited access to healthcare, and may avoid disclosing drug use. Health service utilisation was examined among participants in the Australian Needle and Syringe Program Survey (ANSPS), an annual cross‐sectional sero‐survey of needle syringe program (NSP) attendees. Methods : An anonymous questionnaire was self‐completed by 2, 395 NSP clients throughout Australia. Multivariable logistic regressions identified variables independently associated with (i) disclosure of injecting to the most recent healthcare provider; and (ii) recent presentation to emergency departments. Results : Seventy‐eight percent of participants reported accessing healthcare in the preceding 12 months. Reasons for presentation included general health issues (46%); medication seeking (17%); and both (37%). Participants who recently accessed healthcare or had previously visited their most recent provider were more likely to disclose injecting drug use. Participants presenting to a GP or medical centre were less likely than others to disclose injecting. Those accessing emergency departments were more likely to report recent imprisonment. Conclusions : Despite Australia's universal healthcare system and harm reduction policies, NSP‐participants remain reluctant to disclose injecting, potentially hindering appropriate care and highlighting the need for multiple entry points to the healthcare system, including NSPs and opioid substitution therapy clinics.